1994
DOI: 10.1073/pnas.91.19.8782
|View full text |Cite
|
Sign up to set email alerts
|

On measuring the third dimension of cultured endothelial cells in shear flow.

Abstract: The stress in the endothelial cells induced by blood flow depends on the waviness of the blood-endothelium interface and the slopes at the junctions of neighboring cells in the direction of flow. The height and slope in the third dimension of the living endothelial cells cannot be measured by ordinary optical and electron microscopy. Here we show that interference microscopy meets the challenge. We measured the geometry of cultured confluent human vascular endothelial cells in a flow, and we found that in a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Mechanochemical transduction is proposed to occur when membrane-associated signaling proteins are activated by increases in intramolecular mobility. 17 In light of stress analysis showing that tension is greatest within the cell-cell junctions during the rapid onset of fluid flow, 10 one would expect that structures and/or molecules that are sensitive to fluid shear stress are concentrated at the apex of the apical surface of the cell. 18 Interestingly, PECAM-1 is exclusively localized at the cell-cell apposition site in confluent endothelial cells, and it has long been recognized that direct application of mechanical force results in PECAM-1 tyrosine phosphorylation 19,20 (for review see Fujiwara et al 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanochemical transduction is proposed to occur when membrane-associated signaling proteins are activated by increases in intramolecular mobility. 17 In light of stress analysis showing that tension is greatest within the cell-cell junctions during the rapid onset of fluid flow, 10 one would expect that structures and/or molecules that are sensitive to fluid shear stress are concentrated at the apex of the apical surface of the cell. 18 Interestingly, PECAM-1 is exclusively localized at the cell-cell apposition site in confluent endothelial cells, and it has long been recognized that direct application of mechanical force results in PECAM-1 tyrosine phosphorylation 19,20 (for review see Fujiwara et al 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diameter of arterioles in response to a 1-step increase in intraluminal flow (from 0 to 12 L/min for 5 minutes) were also measured. Isolated arterioles were then incubated with the NO synthase inhibitor L-NAME (10 Ϫ4 mol/L, for 20 minutes), and flow-induced responses were obtained again.…”
Section: Flow/shear Stress-induced Arteriolar Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…PECAM-1 is a scaffold protein able to modulate eNOS activity 51 . Indeed, earlier studies of shear stress distribution in endothelial cell have demonstrated that tension is higher at the level of cell-cell junctions 52 . In addition, in endothelial cells exposed to increasing shear stress, proteins associated with cell-cell junction undergo a rapid reorganization 53 .…”
Section: -Mechanotransduction Of Shear Stress: Role Of the Structurementioning
confidence: 99%
“…34 -42 For instance, altered fluid shear stress influences the activities of mitogen-activated protein kinases 43,44 and G proteins, 45 the production rate of prostacyclin, 46 the activities of growth factors, 26,33,35,47,48 and the morphology 49,50 and cytoskeletal structure 51 of endothelial cells. These changes have been implicated in the mediation of mechanical stress-related vascular atherogenesis.…”
Section: Role Of Signaling Molecules and Growth Factors In Mechanicalmentioning
confidence: 99%